Development and Application of HPLC-MS/MS Method for Determination of Human Pharmaceuticals and Synthetic Hormones in River Water and Sewage Effluents - Al-Odaini, Najat Ahmed (2010)
Pollution of the aquatic environment by residues of human pharmaceuticals and synthetic hormones has become a cause for increasing concern in recent years and acknowledged as one of the most emerging environmental issues. The occurrence of human pharmaceuticals and synthetic hormones in the Malaysian aquatic environment has never been reported. This lack of data could be attributed to the absence of an internationally recognized method for the analysis of pharmaceutical residues in water matrices. The main objective of this study is to develop a sensitive and selective method for the simultaneous determination of 23 pharmaceuticals of interest in environmental matrices such as river water and sewage effluents. The 23 pharmaceuticals consist of different therapeutic classes which include both top prescribed and over the counter (OTC)pharmaceuticals. The developed method was based on sample pre-treatment using Solid Phase Extraction (SPE) followed by analysis using High Performance Liquid Chromatography-Tandem Mass Spectrometry (HPLC-MS/MS). The method was validated and tested against environmental samples. The validation results indicated that the method is able to simultaneously detect and quantify the targeted pollutants with good selectivity and sensitivity. The method performed well for the majority of the pharmaceuticals evaluated, with recoveries greater than 70% for most pharmaceuticals. To the researcher’s knowledge, 5 pharmaceuticals (i.e. amlodipine, chlorpheniramine, chlorothiazide, perindopril and gliclazide) out of the 23 pharmaceuticals had never been analyzed in environmental matrices. The other objectives of this study were to identify and quantify pharmaceuticals residues in environmental samples collected from the Langat River and in effluents of sewage treatment plants (STPs) using the developed method. Seventeen out of twenty-three targeted pharmaceuticals were detected in river water samples namely metformin, atenolol, acetaminophen, metoprolol, mefenamic acid, salicylic acid, salbutamol, perindopril, gliclazide, glibenclamide, loratadine, furosemide, levonorgestrel, cyproterone, diclofenac, chlorothiazide and nifedipine. The median concentration of detected pharmaceutical ranged between less than the Method Detection Limit (<MDL) for furosemide, loratadine and nifedipine to higher concentration of 112.7 ng/L for diclofenac. The highest concentration found was acetaminophen (346.3 ng/L). On the other hand, nineteen targeted pollutants were detected in effluent samples from STPs namely metformin, atenolol, acetaminophen, metoprolol, mefenamic acid, salicylic acid, salbutamol, perindopril, gliclazide, diclofenac, furosemide, chlorothiazide, glibenclamide, lovastatin, loratadine, amlodipine, 17-ethinylestradiol, norethindrone and cyproterone. The median concentration of the detected pollutants were less than the Method Detection Limit (<MDL) for lovastatin, loratadine, norethindrone, cyproterone, amlodipine and 17-ethinylestradiol to a higher concentration of 3270.6 ng/L for metformin. The highest concentration found was metformin (34228.6 ng/L). This study has confirmed that the Malaysian aquatic environment is impacted by pharmaceutical residues at varying levels. Mefenamic acid and Salicylic acid were found to be present in all the river water and STPs effluent samples, suggesting their widespread use and high degree of persistency in the tropical aquatic environment. However, chlorphernamine and simvastatin were not found in any sample for all matrices indicating their high degradability and low persistency in the tropical aquatic environment. Keywords: Human pharmaceuticals, synthetic hormones, water pollution, HPLC- MS/MS, Langat River